2017
DOI: 10.1016/j.jid.2017.01.036
|View full text |Cite
|
Sign up to set email alerts
|

All-Cause and Cause-Specific Mortality in Patients with Psoriasis in Taiwan: A Nationwide Population-Based Study

Abstract: Asian population-based data evaluating all-cause mortality and cause-specific mortality in patients with psoriasis are limited. This study aimed to evaluate the risk of all-cause mortality (stratified according to onset status, disease severity, and concomitant psoriatic arthritis) and cause-specific mortality in patients with psoriasis. Our study cohort consisted of 80,167 patients with newly diagnosed psoriasis between 2001 and 2012 in the National Health Insurance Database. Vital status and cause of death w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 22 publications
5
46
0
Order By: Relevance
“…Absolute and excess risks in these patients with psoriasis were highest for neoplasms; diseases of the digestive, circulatory and respiratory systems; and other diseases of the circulatory system. These findings are consistent with previous studies demonstrating circulatory system diseases and cancer to be among the leading causes of mortality in patients with severe psoriasis . The current study also showed that more patients with psoriasis than controls died at a younger age, as shown previously …”
Section: Discussionsupporting
confidence: 94%
“…Absolute and excess risks in these patients with psoriasis were highest for neoplasms; diseases of the digestive, circulatory and respiratory systems; and other diseases of the circulatory system. These findings are consistent with previous studies demonstrating circulatory system diseases and cancer to be among the leading causes of mortality in patients with severe psoriasis . The current study also showed that more patients with psoriasis than controls died at a younger age, as shown previously …”
Section: Discussionsupporting
confidence: 94%
“…1 Cardiovascular disease deserves special mention in psoriasis, as per results reported in large-scale epidemiological studies. CVD constitutes the first or second cause of mortality (after malignancies) among psoriasis patients, [44][45][46] and the risk is higher among severe patients. 44,45 Duration has also been associated with CVD risk.…”
Section: Psoriasis and Cardiovascular Diseases: What Is The Place Formentioning
confidence: 99%
“…44,45 Duration has also been associated with CVD risk. 1,47 In terms of excess mortality, CVD was attributed globally an excess rate of 1.44 (95% CI: 1.43-1.45) per 1000 person-years; 46 in absolute terms CVD is the main driver of excess mortality in psoriasis. 45 Consistent with these findings, psoriasis patients are at higher risk of cardiovascular events, in particular those with severe disease (RR to general population ranged 1.70-3.04; 1.38-1.59; and 1.37-1.39, for myocardial infarction, stroke and CV mortality, respectively).…”
Section: Psoriasis and Cardiovascular Diseases: What Is The Place Formentioning
confidence: 99%
“…7 While the predominance of early-onset psoriasis was confirmed in samples from dermatology departments, outpatient clinics and self-reported patient surveys, 11,[22][23][24][25][26] recent population-based estimates suggested that late-onset psoriasis was the more common form. [27][28][29] The high frequency of late-onset psoriasis among incident cases probably reflects the underlying population age distribution, with late-onset psoriasis more common as the general population becomes older. The discrepancy could also be explained by over-representation of the more severe early-onset presentation in studies of highly selected populations.…”
Section: Interpretation Of the Findings And Comparison With Existing mentioning
confidence: 99%